2009
DOI: 10.1007/s12565-009-0023-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular embryology for an understanding of congenital heart diseases

Abstract: Congenital heart diseases (CHD) result from abnormal morphogenesis of the embryonic cardiovascular system and usually involve defects in specific structural components of the developing heart and vessels. Therefore, an understanding of "Molecular Embryology", with specific focus on the individual modular steps involved in cardiovascular morphogenesis, is particularly relevant to those wishing to have a better insight into the origin of CHD. Recent advances in molecular embryology suggest that the cardiovascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
0
9
0
2
Order By: Relevance
“…Persistent truncus arteriosus (PTA) is the most severe phenotype of outflow tract (OFT) defects, with an unfavorable prognosis as surgical repair is not always possible (Williams et al, 1999). Although discovering the genetic causes would provide insight into the pathogenesis of CHD, the etiology of most human CHD, including OFT defects, remains unknown because of the multifactorial nature of the diseases, indicating the need for more study (Bruneau, 2008;Olson, 2006;Yamagishi et al, 2009;Zhao and Srivastava, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Persistent truncus arteriosus (PTA) is the most severe phenotype of outflow tract (OFT) defects, with an unfavorable prognosis as surgical repair is not always possible (Williams et al, 1999). Although discovering the genetic causes would provide insight into the pathogenesis of CHD, the etiology of most human CHD, including OFT defects, remains unknown because of the multifactorial nature of the diseases, indicating the need for more study (Bruneau, 2008;Olson, 2006;Yamagishi et al, 2009;Zhao and Srivastava, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…7 Commonly, the clinical phenotype of individuals with GATA6 mutations involves the OFT, but is distinct from that of DiGeorge/22q11.2 deletion syndrome and, rather, manifests as non-syndromic CHD. To date, no molecular link has been demonstrated between GATA6 and TBX1, 8,9 however, a recent study showed that the expression of Sema3c in the OFT was downregulated in mouse embryos deficient for Tbx1, 10 suggesting that GATA6 may share, at least in part, a common molecular pathway with TBX1 during OFT development.…”
mentioning
confidence: 99%
“…7,10 The second heart field is composed of progenitor cells from the medial splanchnic mesoderm adjacent to the pharyngeal endoderm and is the source of the outflow tract (conus cordis and truncus arteriosus) as well as the majority of the right ventricle and atria/ venous pole of the heart. 9,10 The second heart field forms the endothelium, the inner sheath of the cardiac tube and compartments of the heart as they develop.…”
Section: Cardiac Progenitor Cellsmentioning
confidence: 99%
“…Another subset undergoes epithelial-to-mesenchymal transformation and form interstitial fibroblasts and coronary blood vessels including vascular smooth muscle cells and endothelium. 7 A few of the proepicardial cell precursors differentiate into myocytes located in the muscular ventricular septum and atria. 5,26 …”
Section: Cardiac Progenitor Cellsmentioning
confidence: 99%